STUDY QUR'AN: The Quarantine Program for Memorizing the Qur'an Effectively at Madrasatul Qur'an Islamic Pesantren Mambaul Falah Tambilung Tambak Bawean Gresik - Ahmad Halid (Studia Quranika, 2023)
The process of memorizing the Al-Qur'an generally takes a long time, but at Madrasatul Qur'an the Mambaul Falah Islamic Boarding School Tambilung Tambak Bawean Gresik has a quarantine program in the process of memorizing the Qur'an quickly. This quarantine program is very interesting, because students are motivated to memorize quickly. The focus of this research is how the Al-Qur'an Memorization Quarantine Program students can memorize the Al-Quran in a relatively short time. Through field research and using qualitative methods, descriptive, and data sources using observation and interviews, and analyzed using the Miles and Huberman model, and the validity of the data using source triangulation. The results of this study are that the quarantine program for memorizing the Al-Qur'an is very effective because students are focused only on memorizing the Al-Qur'an and are guided continuously by ustadz with core programs and companions or supports.